Crop Diversification and Intensification through Community Vegetable Production Trial in a Village of Dingaputa Haor (Journal of Environmental Science and Natural Resources, 2015)
A study was conducted at Purba Tethulia village, in Dingaputa haor of Mohangonj Upazila in Netrakona district during the period from April 2011 to March 2012. The objective of the study was to diversify and intensify crops in the research site, to utilize waste/fallow area of homestead land and to utilize family labour during the lean season. The study included community production trials on year round vegetable (Indian spinach, sweet gourd, ash gourd, snake gourd, country bean, bottle gourd) covering all 462 households of the research site. The highest gross margin (Tk 640 farm-1) was obtained from country bean during the winter and Tk 399 farm-1 for snake gourd during the summer. The homestead vegetables production round the year may be extended to the haor areas of similar environment for food security as well as for the income generation of the poor and extreme poor people.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22145 J. Environ. Sci. & Natural Resources, 7(1): 59-61 2014